Effectiveness of a pelvic floor muscle exercise intervention in improving knowledge, attitude, practice, and self-efficacy among pregnant women: a randomized controlled trial - Alagirisamy, Parwathi; Mohd Sidik, Sherina; Rampal, Lekhraj; Ismail, Siti Irma Fadhilah (Korean Academy of Family Medicine, 2022)
Background: The awareness and practice of pelvic floor muscle exercise (PFME) in the prevention and reduction of the rate of urinary incontinence among pregnant women was considerably poor, despite the increased prevalence of urinary incontinence during pregnancy across Malaysia. There healthcare providers do not give adequate attention to the potential impact of PFME on urinary incontinence and there is limited local intervention addressed urinary incontinence during pregnancy. The objective of this study was to determine the effectiveness of a newly developed PFME intervention in terms of knowledge, attitude, practice, self-efficacy, and urinary symptoms. Methods: A single-blinded, two-armed, randomized control trial was included pregnant women from 18 to 20 weeks of gestation and was conducted at the Maternity Hospital of Kuala Lumpur. The intervention group received PFME in addition to the usual perinatal care. The data were collected using validated questionnaires at 4 time points: baseline, post-intervention in the early third trimester, late third trimester, and early postnatal period. The intervention effects were analyzed using a generalized estimating equation. Results: The primary analysis included pregnant women who had at least one follow-up; 122 women (71.8%) in the intervention group had significant improvement in knowledge, attitude, practice, and self-efficacy, as well as in the severity of urinary incontinence over time. However, improvement was not observed in self-reported urinary incontinence. Conclusion: PFME can be considered an effective initial intervention to provide information about urinary incontinence prevention to pregnant women.